Estimating the public health impact of a national guideline on cervical cancer screening: an audit study of a program in Campinas, Brazil - Diama Bhadra Vale; Talita Lourenço Menin; Joana Froes Bragança; Julio Cesar Teixeira; Lucas Almeida Cavalcante; Luiz Carlos Zeferino (BMC Public Health, 2019)
Abstract Background A Brazilian guideline on cervical cancer screening was released in 2011. The objective was to verify changes in screening indicators around this period. Methods An audit study which sample was all screening tests performed by the public health system of Campinas city from 2010 to 2016. Variables were absolute tests numbers, excess tests, intervals and results, by age. For trend analysis was used Cochran-Armitage × 2 and linear regression. Results Were carried out 62,925 tests in 2010 and 43,523 tests in 2016, a tendency at a reduction (P = 0.001). Excess tests were higher than 50% over the years, with a tendency at a reduction (P < 0.001). Tests performed on women under 25 ranged from 20.2 to 15.4% in the period (P < 0.001), while in the 25–64 years age-group, it ranged from 75.1 to 80.2% (P < 0.001). In 2010 the most frequent interval was annual (47.5%) and in 2016 biennial (34.7%). There was a tendency at a reduction in the proportion of tests performed at the first time and those with an annual interval (P < 0.001), and also a tendency at an increase in tests with intervals equal to or greater than biannual (P < 0.001). We observed a tendency at a reduction in LSIL and HSIL-CIN2 results (P = 0.04 and P = 0.001, respectively), and a tendency at an increase in HSIL-CIN3 result (P = 0.02). Conclusion The proportion of cervical cancer screening tests performed out of the recommendation showed a significant reduction in the period. This indicates a tendency to align cervical cancer screening in Campinas with the standards recommended.